Antiproliferative activity of buttermilk lipid fractions isolated using food grade and non-food grade solvents on human cancer cell lines. (1st December 2016) - Castro-Gómez, Pilar; Rodríguez-Alcalá, Luis M.; Monteiro, Karin M.; Ruiz, Ana L.T.G.; Carvalho, João E.; Fontecha, Javier
Highlights: Buttermilk is a source of MFGM polar lipids that may contribute as a nutraceutical. Food grade solvent lipid extract show antiproliferative activity on cancer cells. Phospho- and sphingolipids seems crucial for the antiproliferative activity. Lipid extracts from buttermilk could be a valuable functional food ingredient. Abstract: Buttermilk is a dairy by-product with a high content of milk fat globule membranes (MFGMs), whose protein constituents are reported to be antiproliferative. Lipids represent about half of the composition of MFGM. The aim of this study was to isolate buttermilk lipid fractions and evaluate their potential antiproliferative effect. Selective extraction with food grade or non-food grade solvents was performed. Antiproliferative effectiveness of lipid extracts and their neutral and polar fractions was evaluated on nine human cancer cell lines. Fractions obtained using food grade ethanol gave a higher yield than those obtained using non-food grade solvents, and they effectively inhibited cell viability of the cancer cell lines investigated. These fractions, rich in phospho- and sphingolipids, were strongly antiproliferative against human ovary and colon cancer cells. This observation allowed us to hypothesize further analyses aimed at promoting the use of buttermilk polar lipid fractions as functional food additives.